Magnifier or refractor? Exploring the impact of geographical indication on people’s perception of the value of cultural ecosystem services based on the SolVES model - Luo, Youyu; Xu, Huilin; Zhang, Junjie; Chen, Nan; Ye, Haiyan; Lei, Wenyan (Frontiers in Ecology and Evolution, 2023)
[Purpose/Significance] To a certain extent, Geographical Indication (GI) protects the ecosystem of product origin, but there is still a lack of quantitative evidence on its cultural spillover effect. The mechanism of the impact of geo-certified landscapes on people's perceived value of cultural ecosystem services (CESs) should be explored. [Methods/Procedures] In this study, two urban forest parks, Changqing and Zhongshan, which differ mainly in terms of geo-certified landscapes, were selected in Beihai, Guangxi. Basically, homogeneous volunteers were recruited, and photos of value labels were collected from their independent visits to two parks. The SolVES model was used to explore the effect of the presence or absence of geo-certified landscapes in urban park ecosystems on people's CESs needs and the relation to the spatial context of the landscape. [Results/Conclusions] The results show that GI significantly enhance people's perception of human CESs value of landscape elements, and clarifies the correspondence perception relationship between CESs value types and each landscape element. In addition to the spillover effect on humanistic value perception, GI also attracts and transfers people's aesthetic attention to the natural landscape itself to a certain extent. And these two effects will also spread to the ecosystem that the landscape belongs to.